Research Trends on Online Learning Toward Changes in Millennial Consumer Behavior in the Digital Era: A Bibliometric Analysis - Purbokusumo, Andreas Sang Aji; Wajdi, M. Farid; Sholahuddin, Muhammad; Fadloli, F (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of digital technology, which affects almost every aspect of life, has also transformed the consumption behavior of the millennial generation toward digital domains. This study aims to analyze trends and changes in millennial consumer behavior in the digital era as an impact of online learning. Using bibliometric methods and VOSviewer visualization, data were collected from international publications (Scopus, Web of Science, Google Scholar) during the 2020-2025 period. The findings show that online learning has accelerated the adoption of digital consumption behaviors among millennials, with key terms such as consumer behavior, machine learning, e-commerce, and millennial forming interconnected clusters. The study also identifies a research gap related to loyalty and postpurchase behavior among millennials in the digital ecosystem. The results of this research are expected to serve as a reference for strengthening educational policy, digital economy development, and digital literacy to support the national agenda for superior human resource development and digital transformation in Indonesia.